2008
DOI: 10.1530/eje-07-0633
|View full text |Cite
|
Sign up to set email alerts
|

Implication of lipocalin-2 and visfatin levels in patients with coronary heart disease

Abstract: Objectives: Visfatin and lipocalin-2 are novel adipokines associated with insulin resistance (IR) and obesity-related metabolic disorders. We compared lipocalin-2 and visfatin concentrations between patients with coronary heart disease (CHD) and control subjects and evaluated their association with cardiovascular risk factors. Methods: We examined serum visfatin, lipocalin-2 levels, and cardiovascular risk factors in 91 subjects (49 patients with angiographically confirmed CHD versus 42 age-and gender-matched … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
81
1
3

Year Published

2008
2008
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(91 citation statements)
references
References 22 publications
(28 reference statements)
6
81
1
3
Order By: Relevance
“…The results of our study are suggestive of increased serum visfatin levels as an indicator of coronary artery disease (3,7,8,(13)(14)(15)(16)20,24,26,30,32,33,36) . The association has been first identified in patients with carotid artery disease (2,14) and results of different studies including visfatin and coronary artery disease have been published in recent years (7,15,26,27) .…”
Section: Discussionsupporting
confidence: 58%
See 2 more Smart Citations
“…The results of our study are suggestive of increased serum visfatin levels as an indicator of coronary artery disease (3,7,8,(13)(14)(15)(16)20,24,26,30,32,33,36) . The association has been first identified in patients with carotid artery disease (2,14) and results of different studies including visfatin and coronary artery disease have been published in recent years (7,15,26,27) .…”
Section: Discussionsupporting
confidence: 58%
“…The findings of our study population when compared with the controls supported a prominent endothelial dysfunction in the study group. However, in a study by Choi et al (24) , circulating visfatin levels were not found to be significantly related with cardiovascular risk factors such as obesity, hypertension, lipid profile, and insülin resistance. Additionally, the auhors findings were not significantly different between patients with heart disease and control subjects (24) .…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Previous studies on diabetes (Kang et al, 2010) and CHD (Choi et al, 2008) have reported a positive correlation between the serum visfatin levels and insulin resistance; moreover, Chang et al (2010) discovered a positive correlation between the visfatin mRNA expression in visceral adipose tissues and insulin resistance. The results of our study are in accordance with these results; that is, the IRI was positively correlated with the serum visfatin levels in patients with CAC, indicating the important role played by visfatin in the insulin-resistance mechanism.…”
Section: Discussionmentioning
confidence: 82%
“…In the study by Choi et al (37), serum NGAL levels were determined to be significantly higher in patients with CAD than in the healthy population. Similarly in another study, serum NGAL levels showed an increasing tendency in CAD and AMI, although this was not significant.…”
Section: Discussionmentioning
confidence: 95%